Role of ZrO2 on Cu/ZnO/Al2O3/ZrO2 in Methanol Synthesis - Jung, Heon; Yang, Dae Ryook; Jung, Kwang-Deog (WILEY-V C H VERLAG GMBH, 2015)
Cu/ZnO/Al2O3/ZrO2 (CZAZr) catalysts were prepared by a coprecipitation method. CO2 was introduced into aging solution to get CZAZr precusors with malachite phase. The x value in CZAZr(x) is the metallic ratio of the Zr component at a fixed metallic ratio of Cu:Zn:Al of 6:3:1. TOFMeOH of CZAZr(0) was 0.56 mu mol/m(2)Cu/s at 250 degrees C, 50 atm and a gas hourly space velocity (GHSV) of 12 000 mL/g(cat)/h. TOFMeOHs of CZAZr(1), CZAZr (2), CZAZr(3), and CZAZr(4) were 0.64, 0.90, 0.99, and 1.08 mu mol/m(2)Cu/s at the same reaction condition, respectively. TOF(MeOH)s of CZAZr catalysts increased with increasing ZrO2 content, indicating that high TOFMeOH of CZAZr catalysts came from ZrO2 as compared with CZAZr(0) catalysts. These kinetic data on CZAZr catalysts in the practical reaction condition proved the suggestion from previous infrared (IR) study on Cu/Zr catalysts. ZrO2 afforded the adsorption sites for CO and CO2 insertion into Zr-OH and Cu supplied active hydrogen to ZrO2 for hydrogenating formate and hydroxycarbonate to methanol on ZrO2 in addition to methanol synthesis on Cu/ZnO/Al2O3.
Keywords: COPPER CATALYST; METAL-OXIDES; HYDROGENATION; PRECURSOR; MALACHITE; GAS; ZNO; CO